Direct trifluoroethylation of carbonyl sulfoxonium ylides using hypervalent iodine compounds - Echemendía, Radell; Montgomery, Carlee A.; Cuzzucoli, Fabio; Burtoloso, Antonio C. B.; Murphy, Graham K. (Beilstein Journal of Organic Chemistry, 2024)
A novel study on the hypervalent iodine-mediated polyfluoroalkylation of sulfoxonium ylides was developed. Sulfoxonium ylides, known for their versatility and stability, are promising substrates for numerous transformations in synthetic chemistry. This report demonstrates the successful derivatization of sulfoxonium ylides with trifluoroethyl or tetrafluoropropyl groups, and provides valuable insights into the scope and limitations of this approach. Nineteen examples have been prepared (45–92% yields), with structural diversity modified at two key sites on the sulfoxonium ylide reactants. Finally, DFT calculations provided insights about the mechanism of this transformation, which strongly suggest that an SN2 reaction is operative.
Keywords: alkylation; DFT calculations; fluorine chemistry; hypervalent iodine; sulfoxonium ylide; sulphur ylides